Zirconia dental implants: where are we now, and where are we heading?. Issue 1 (February 2017) - Cionca, Norbert; Hashim, Dena; Mombelli, Andrea
Abstract: Despite decades of titanium as the gold standard in oral implantology, the search for alternatives has been growing. High esthetic standards and increasing incidence of titanium allergies, along with a rising demand for metal‐free reconstructions, have led to the proposal of ceramics as potential surrogates. Following numerous experimental studies, zirconium dioxide (zirconia) has earned its place as a potential substitute for titanium in implantology. Yet, despite zirconia's excellent biocompatibility and tissue integration, low affinity to plaque and favorable biomechanical properties, early failures were significantly higher for zirconia implants than for titanium implants. Technical failure as a result of fracture of the material is also a major concern. So far, zirconia implants have been mainly manufactured as one‐piece implant systems because of the material's limitations. Nevertheless, various two‐piece systems have been progressively emerging with promising results. Screw‐retained abutments are desirable but present a major technical challenge. Innovation and technical advances will undoubtedly lead to further improvement in the reliability and strength of zirconia implants, allowing for novel designs, connections and reconstructions. Additional clinical studies are required to identify all relevant technical and biological factors affecting implant success and patients' satisfaction. However, the evidence for a final verdict is, at present, still incomplete.